Study of the relationship between nutrition, physical activity and overweight/obesity in children in a school context: Study of the relationship between nutrition, physical activity - Yous, Fouzia; Zaabar , Salim; Adjeroud-Abdellatif, Nawal; Guemouni , Sara; Kerrour, Nesrine Sana; Madani, Khodir (The North African Journal of Food and Nutrition Research, 2023)
Aim: The objective of this study is to describe the behavior, eating habits and lifestyle of schoolchildren from different regions of Bejaia, and to evaluate their food consumption on the one hand, and their level of physical activity (PAL) on the other hand. Methods: Children (n=240, F/G = 120/120), aged 6 to 12 years, enrolled in different institutions (primary, secondary) in the different regions of Bejaia, participated in this study. The weight and height of the children were measured (BMI), and their eating habits and physical activity were assessed using adapted questionnaires. Food consumption was estimated by the 24-hour recall method. Results: The results show an observable growth of BMI, with age, height and especially weight, BMI is high in overweights and obese children compared to normo-weight children, in both sexes, PAL evaluation in both categories (overweight/ normal weight) (girls/boys) shows that PAL is low in overweight and obese children (1.69) compared to normal weight children (2.29), Correlation test showed that there is a positive correlation between BMI and PAL in both sexes. According to the results of the food habits, the frequency of consumption of the different food products according to their types are as follows: in the overweight and obese children we find an excess of consumption of these types of food (carbohydrate, lipid), on the other hand in the normo-weight children we find a balance in the consumption of these types of food. Conclusion: This study shows that overweight and obesity exist, which confirms the nutritional transition. Children have bad eating habits (snacking between meals, consumption of fast food and sugary drinks), all these habits associated with sedentary activities, may be factors promoting obesity.